"Messy Solidarities": Reflections on the Politics of the Present. Issue 1 (3rd April 2022) - Nasta, Susheila
Abstract: This essay reflects on the history of anti-racist politics and activism in Britain following the impact of the Black Lives Matter movement in the US. Examining the history of the literary magazine Wasafiri, it offers insights into how the different nomenclatures for 'black' and 'Asian' emerged at different moments in time. It provides a series of autobiographical pathways into this material, arguing that we should not forget the past to move forward in the present.